Intravitreal injection of forskolin, homotaurine, and L-carnosine affords neuroprotection to retinal ganglion cells following retinal ischemic injury - Russo, Rossella (Mol Vis, 2015)
PURPOSE: Retinal ganglion cell (RGC) death is the final event leading to visual impairment in glaucoma; therefore, identification of neuroprotective strategies able to slow down or prevent the process is one of the main challenges for glaucoma research. The purpose of this study was to evaluate the neuroprotective potential of RGC death induced by the in vivo transient increase in intraocular pressure (IOP) of a combined treatment with forskolin, homotaurine, and L-carnosine. Forskolin (7beta-acetoxy-8, 13-epoxy-1a, 6β, 9a-trihydroxy-labd-14-en-11-one) is an activator of adenylate cyclase that decreases IOP by reducing aqueous humor production and functions as a neuroprotector due to its neurotrophin-stimulating activity. Homotaurine is a natural aminosulfonate compound endowed with neuromodulatory effects, while the dipeptide L-carnosine is known for its antioxidant properties. METHODS: Retinal ischemia was induced in the right eye of adult male Wistar rats by acutely increasing the IOP. Forskolin, homotaurine, and L-carnosine were intravitreally injected and RGC survival evaluated following retrograde labeling with FluoroGold. Total and phosphorylated Akt and glycogen synthase kinase-3β (GSK-3β) protein levels, as well as calpain activity, were analyzed with western blot. Protein kinase A (PKA) was inhibited by intravitreal injection of H89. RESULTS: A synergic neuroprotective effect on RGC survival was observed following the combined treatment with forskolin, homotaurine, and L-carnosine compared to forskolin alone. The observed neuroprotection was associated with reduced calpain activity, upregulation of phosphoinositide 3-kinase (PI3K)/Akt pathway, and inhibition of GSK-3β but was independent from PKA activation and distinct from the hypotensive effects of forskolin. CONCLUSIONS: A multidrug/multitarget approach, by interfering with several pathways involved in RGC degeneration, may be promising to achieve glaucoma neuroprotection.